Raised levels of agalactosyl IgG in childhood tuberculosis - (:unkn) unknown (ROYAL SOC TROPICAL MEDICINE, 1996)
Raised levels of agalactosyl immunoglobulin G (IgG) have been found in adults with tuberculosis, Crohn's disease and rheumatoid arthritis, and recent evidence, both circumstantial and experimental, suggests that it has distinct functional properties that play a role in pathogenesis. Since tuberculosis in infants is strikingly different from the disease seen in adults, but switches to the adult form at adrenarche or puberty, we documented the association of agalactosyl IgG with tuberculosis in childhood between the ages of 0 and 16 years. Sera were collected from 99 children diagnosed as cases of tuberculosis in Istanbul, Turkey, and compared with levels in non-tuberculous controls. The percentage of agalactosyl IgG was significantly raised in children with tuberculosis overall (P<0.001, Mann-Whitney U test) and in all age groups except for children over 12 years old, whose numbers were too small to be meaningful. Therefore the differences between adult and childhood tuberculosis are not due to a difference in the tendency for agalactosyl IgG to be produced at different ages. The percentage of agalactosyl IgG may be useful for monitoring the progress of individual complicated cases.
Keywords: tuberculosis; serum agalactosyl IgG; children; RHEUMATOID-ARTHRITIS; SERUM IGG; GALACTOSYLATION; DISEASE